Post-Traumatic Stress, Job Stressors, Psychological Capital and Job Outcomes: A Study of Pakistan Employees living under ongoing terrorism. (3rd April 2021) - Junaid, Fatima A.; Haar, Jarrod; Brougham, David
ABSTRACT: This study investigates the influence of Post-Traumatic Stress Disorder (PTSD) due to prolonged exposure to terrorism, on job satisfaction and turnover intentions. With our focus on organisational life, which is not without job stressors, the present study looks to understand how job stressors interact with PTSD and influence employees' job satisfaction and turnover intentions. We draw on Conservation of Resources (CoR) theory to understand how these stressors drain employee resources, leading to poorer job outcomes. Building on CoR, we argue that employee Psychological Capital (PsyCap) might provide some respite for employees and reduce the detrimental influences of PTSD on job satisfaction and turnover intentions. We conducted a moderated-moderated-mediated analysis, looking at the role of stressors and PsyCap on PTSD and employee outcome relationships, by exploring job stressors moderating the influence of PTSD on the mediator (PsyCap) through to outcomes. The study was conducted in Pakistan, providing the context of prolonged exposure to terrorism. Using data from 416 Pakistan employees, we find consistent effects supporting our hypotheses. While the stressors typically drain resources, PsyCap does mediate these effects and significant moderated-moderated-mediation effects aid our understanding of how these relationships ultimately influence job outcomes.